Обрядовое использование стрел в культурах эпохи поздней бронзы юга Восточной Европы - Цимиданов, В.В. (Материалы по археологии Северного Причерноморья, 2015)
The ritual use of arrows in the Late Bronze Age cultures of South East Europe is studied in this article. The author analyzes the burials and settlements cult complexes of some cultures (Timber Grave, Sabatinovka, Noua, Chisinau-Korlaten, Belozerka) in which there were fragments of the arrows. As a result of analysis of these complexes several conclusions were made, the most important of them are the following: a) arrows was associated with fire and, possibly, sun; they were sacrificed to the fire; b) arrows function as mediators with the other world; they used for contacts with deities; c) arrows were made of different manipulations during rites; they were stuck in the ground and broke; arrowheads were placed in vessels; d) when people left the building, they used arrows as victims; e) arrows was associated with male sexual power; f) arrows were used as amulets; these were placed on the boundaries of different objects for protection against demonic forces.